Gazelles, Industry Growth and Structural Change - Jaap W.B. Bos; Erik Stam (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2011)
This paper examines to what extent gazelles are the drivers of the growth of industries and structural change. To this purpose we analyze gazelles over a 12 year period (annually from 1997 until 2008) in the Netherlands, and relate them to the dynamics in employment per industry. We use a panel vector autoregressive (PVAR) model to explore the relations between the presence of gazelles and industry (employment) growth (with 43 two digit industries). An increase in the presence of gazelles in an industry appears to have a positive effect on the subsequent growth of the industry. We do not find evidence for an inverse causal relation: there are no long run positive effects of increases in industry growth on the presence of gazelles. There is also no relation between the overrepresentation of gazelles and subsequent industry growth.
Keywords: 330; entrepreneurship; gazelles; industry growth; structural economic change